Evaluation of Commercial Tomato Hybrids for Climate Resilience and Low-Input Farming: Yield and Nutritional Assessment Across Cultivation Systems - Maria Gerakari; Diamantia Mitkou; Christos Antoniadis; Anastasia Giannakoula; Stefanos Stefanou; Zoe Hilioti; Michael Chatzidimopoulos; Maria Tsiouni; Alexandra Pavloudi; Ioannis N. Xynias; Ilias D. Avdikos (Agronomy)
Commercial tomato hybrids exhibit robust performance in modern high-input agricultural systems. However, their suitability for low-input farming remains uncertain. With the goal that by 2030, 25% of European agricultural production must be organic as part of the European Green Deal, this study aims to assess whether existing commercial tomato hybrids can offer a viable solution for low-input farming. Additionally, the impact of beneficial microorganisms such as plant growth-promoting rhizobacteria (PGPR), in relation to the growth and productivity of tomato hybrids under low-input cultivation is assessed. For this purpose, a well-defined microbial consortium, including Azotobacter chroococcum, Clostridium pasteurianum, Lactobacillus plantarum, Bacillus subtilis, and Acetobacter diazotrophicus, was applied as a liquid suspension to enhance root colonization and promote plant growth. Seven commercial tomatoes (Solanum lycopersicum L.) hybrids—the most popular in the Greek market—were evaluated for their performance under high-input (hydroponic) and low-input cultivation systems (with and without the use of PGPR). Several parameters related to yield, fruit quality, nutritional value, descriptive traits, and leaf elemental concentration were evaluated. In addition, a techno-economic analysis was conducted to assess whether hybrids developed under high-input conditions and intended for such cultivation environments suit low-input farming systems. The results indicated that such hybrids are not a viable, efficient, or profitable strategy for low-input cultivation. These findings underscore the importance of breeding tomato varieties, specifically adapted to low-input farming, highlighting the need for targeted breeding strategies to enhance sustainability and resilience in future agricultural systems. Notably, this study is among the first to comprehensively assess the response of commercial tomato hybrids under low-input conditions, addressing a critical gap in the current literature.